Information Rigidities and Exchange Rate Expectations - Joscha Beckmann; Stefan Reitz (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Sluggish adjustment of expectations to new information is rational in an environment characterized by information costs and signal-to-noise problems. This paper investigates the role of such information rigidities for exchange rate expectations using data from Consensus Economics for eight emerging and industrial economies from 1999 until 2015. Our results provide strong support for this view showing that the inclusion of forecast updates largely accounts for otherwise detected biases in expectation errors. Moreover, we detect little evidence for a systematic effect of fundamentals or uncertainty measures on exchange rate disagreement. Structural shocks do not appear to lead to any systematic increase in disagreement which illustrates the importance of noisy information models.
Keywords: F31; F37; G17; 330; Exchange rates; Expectations; Disagreement